Analisis Pengaruh Penambahan Reflector Terhadap Tegangan Keluaran Modul Solar Cell - Prastica, Reynaldo Hilga Adis; , Hasyim Asy'ari S.T., M.T (2016)
In this era, all of the people survival can not be separated from the electrical energy, from the people who live in villages and are living in a big city. The power plant is now a conventional power plants that use fossil fuels in the process. While on the other hand, the availability of fossil fuels will gradually be depleted so we needs the required of new power plants that do not use fossil fuels in the process. Solar cell module is a tool that can convert sunlight into electric power. Sunlight is a source of renewable energy that can be utilized as a new power plant. But in the process it takes certain additions to the solar cell module so the output voltage is generated can be optimized. This study aimed to determine the effect of the mirror reflector of the output voltage produced by the solar cell module. Module of solar cells are used as many as 3 pieces of the capacity of 120 Wp. Tests are conducted from 09.00 s/d 16.00, for 3 days without a reflector and 3 days using a reflector with different tilt angles. This study uses a reflector with a slope angle of 65º, 75º, and 85º. Solar cell module without reflector produces the highest output voltage of 20.4 V. While the results of the output voltage of the solar cell module by using a maximum of 20,7 V reflector at an angle of 75 °. The results of this study show that the addition of the reflector can improve the output voltage of solar cell module.